The little book of surgical cartoons - Perelygin, Evgeniy E. (tfm Publishing, 2016)
Evgeniy Perelygin -- a surgeon who is known to his friends as Perya -- has managed to capture the funny, the amusing, and the ridiculous aspects of what surgeons do and think. Yes, surgeons take their profession very seriously and their patients even more so. But, what is true in any aspect of human life is also true for surgery -- there is always something to laugh about, or even ridicule. And this includes, above all, surgeons themselves! In each of these cartoons lurks the kernel of a basic surgical truth. This truth has been blown up, distorted, and exaggerated, but remains at the heart of the picture. Each picture has a legend describing the situation, which is followed by an aphorism, quote, or comment. This book is essentially for surgical eyes -- they are all cutting edge, and will have the reader in stitches.